2D Porphyrinic Metal–Organic Framework Nanosheets as Multidimensional Photocatalysts for Functional Materials. Issue 42 (14th September 2021) - Zhang, Liwen; Ng, Gervase; Kapoor‐Kaushik, Natasha; Shi, Xiaobing; Corrigan, Nathaniel; Webster, Richard; Jung, Kenward; Boyer, Cyrille
Abstract: Ultrathin porphyrinic 2D MOFs, ZnTCPP nanosheets (TCPP: 5, 10, 15, 20‐(tetra‐4‐carboxyphenyl) porphyrin) were employed as heterogeneous photocatalysts to activate PET‐RAFT polymerization under various wavelengths ranging from violet to orange light. High polymerization rates, oxygen tolerance, and precise temporal control were achieved. The polymers showed narrow molecular weight distributions and good chain‐end fidelity. The 2D ZnTCPP nanosheets were applied as photocatalysts in stereolithographic 3D printing in an open‐air environment under blue light to yield well‐defined 3D printed objects. Apart from providing an efficient catalytic system, 2D ZnTCPP nanosheets reinforced the mechanical properties of the 3D printed materials. The presence of ZnTCPP embedded in the materials conferred effective antimicrobial activity under visible light by production of singlet oxygen, affording 98 % and 93 % anti‐bacterial efficiency against Gram‐positive and Gram‐negative bacteria, respectively. Abstract : 2D porphyrinic nanosheets were investigated as heterogeneous photocatalysts to mediate PET‐RAFT polymerization of different monomers under a broad range of light wavelengths. This system exhibits oxygen tolerance and temporal control resulting in the preparation of well‐defined polymers. Nanosheets were utilized to catalyze stereolithographic 3D printing, providing reinforced mechanical properties and effective antimicrobial activity.